Telkomsel Halo Product Marketing Communication Strategy at PT. Medan Marelan Regional Office Cellular Telecommunications - Atika Dewi, Nurhaliza (Pena Cendekia Insani, 2023)
Telkomsel is currently improving and strengthening their brand by releasing independent products and products that are widely used by people today. In order for the sales level to reach the target, Telkomsel requires an effective marketing communication strategy in order to satisfy and define consumers. In this study the researchers chose the Halo card product at PT. Telecommunications Seluler Medan Marelan regional office, which can be seen in their high level of sales of their products, one of which is Telkomsel Halo. Based on this background, the question arises how the marketing communication strategy is used in marketing Telkomsel Halo products and what is consumer behavior towards the Halo Telkomsel product. So in this study the aim is to describe the marketing communication strategies used by Telkomsel in marketing Halo products in order to attract and set consumer targets and to know consumer behavior towards Telkomsel Halo products. This type of research is qualitative with a symbolic interaction approach where the data is determined through observation, interviews, and documentation directly in the field. The theory used is integrated marketing communication (IMC) theory. The results of this study can be concluded that the marketing communication strategy used in marketing Telkomsel Halo products at the Medan Marelan regional office uses the theory of integrated marketing communication marketing strategy which consists of 6 components, namely advertising, direct marketing, interactive marketing, sales promotion, public relations and personal selling. In addition, several factors were found that influence consumer behavior towards Telkomsel Halo products, namely internal factors and external factors.